PRIMARY SCHOOL SYSTEM IN JAVA BEFORE AND UNDER JAPANESE OCCUPATION (1940-1944) - Ramli, Murni (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
Primary School before and during the Japanese occupation of Indonesia has not been studied comprehensively due to the paucity of authentic data. The Japanese military document called â€˜Jawa ni okeru bunkyÅ no gaikyÅâ€™ has served as an important source in this field. This study analyzes the alteration of primary school and its re-establishment process following the example of the educational system employed in imperial Japan. The number of primary schools has been reported to decline dramatically - either the number of schools or that of the students. However, we[who?] found that the number of primary schools did not significantly decrease, and, even more, the number of students increased in Java. One teacher two classes system and the one room two classes were introduced in response to the teacher shortage. The curriculum had been Japanisized through introducing new subjects such as Japanese language, spirit/mental education, physical education and vocational activities. Japanese primary school emphasizes practical education unlike the Dutch system which merely fosters and nurtures the academic side.